Implementation of the Pancasila Student Profile Strengthening Project Through the Utilization of Pine Fruit Waste for Entrepreneurial Skills - Sari, Anggun Yunista; Minsih, M (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to elucidate the implementation of the Pancasila Student Profile Strengthening Project (P5) in fostering entrepreneurial skills among elementary school students and to analyze its impact on the development of those skills, particularly through the utilization of pine fruit waste. Methodology: A qualitative descriptive approach with a case study design was applied. Data were gathered using interviews, observations, and document analysis. The research subjects included the school principal, three classroom teachers (grades 4–6), nine students, and supporting documents such as P5 modules and student project outcomes. Data validity was ensured through triangulation of techniques and sources. Results: The study found that the implementation of P5, from planning to execution, was conducted effectively. The project significantly contributed to students' entrepreneurial competence, including creativity, decision-making, problem-solving, independence, and collaboration. Key success factors included strong involvement of school leadership, teacher engagement, the formation of positive habits, and parental support. However, challenges were noted in areas such as teachers’ limited understanding of P5, technological adaptation, student skill variation, and marketing of products. Applications/Originality/Value: This research provides a practical reference for integrating entrepreneurship within character education using local resources. It demonstrates how the P5 framework can serve as a strategic vehicle for instilling 21st-century competencies in elementary school students through project-based learning rooted in contextual relevance.